Monopoly Power and Distribution in Fragmented Markets : The Case of Groundwater - Jacoby, Hanan G. (World Bank, Washington, DC, 2014)
Using data from Pakistan's Punjab, the authors examine monopoly power in the market for groundwater - irrigation water extracted using private tubewells - a market characterized by barriers to entry and spatial fragmentation. Simple theory predicts that tubewell owners should price-discriminate in favor of their own share tenants. And this analysis of individual groundwater transactions over an 18-month period confirms such price discrimination. And among those studied, tubewell owners and their tenants use considerably more groundwater on their plots than do other farmers. The authors also provide evidence that monopoly pricing of groundwater leads to compensating - albeit small - reallocations of canal water, which farmers exchange in a separate informal market. Despite the substantial misallocation of groundwater, a welfare analysis show that monopoly pricing has limited effects on equity and efficiency. In the long run, a policy aimed at eliminating monopoly pricing would do little to help the poorest farmers.